2022
DOI: 10.3390/foods11244097
|View full text |Cite
|
Sign up to set email alerts
|

Application of Exogenous Melatonin Improves Tomato Fruit Quality by Promoting the Accumulation of Primary and Secondary Metabolites

Abstract: Melatonin plays key roles in improving fruit quality and yield by regulating various aspects of plant growth. However, the effects of how melatonin regulates primary and secondary metabolites during fruit growth and development are poorly understood. In this study, the surfaces of tomato fruit were sprayed with different concentrations of melatonin (0, 50, and 100 µmol·L−1) on the 20th day after anthesis; we used high-performance liquid chromatography (HPLC) and liquid chromatography/mass spectrometry (LC/MS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…The foliar application with acetyl salicylic acid reduced the titratable acidity (Meena et al, 2017), also potassium silicate reduced titratable acidity under chilling conditions (Alkharpotly and Abdelrasheed, 2021). Dou et al (2022) reported that exogenous melatonin application clearly reduced the acidity content in tomato fruits.…”
Section: Chemical Composition Of Fruitsmentioning
confidence: 99%
“…The foliar application with acetyl salicylic acid reduced the titratable acidity (Meena et al, 2017), also potassium silicate reduced titratable acidity under chilling conditions (Alkharpotly and Abdelrasheed, 2021). Dou et al (2022) reported that exogenous melatonin application clearly reduced the acidity content in tomato fruits.…”
Section: Chemical Composition Of Fruitsmentioning
confidence: 99%
“…Primarily, melatonin has been extensively researched for its role in enhancing tomato resistance to various abiotic stresses, encompassing drought [41,42], heavy metals [43,44], heat damage [45], cold damage [46], salt damage [47], and more. Furthermore, the melatonin treatment of tomatoes has been found to delay leaf senescence [48], boost tomato disease resistance [49,50], and improve tomato fruit quality [51,52]. Concurrently, research has revealed that melatonin treatment can induce the accumulation of nitric oxide (NO) and influence the development of adventitious roots in tomato seedlings [37].…”
Section: Introductionmentioning
confidence: 99%
“…Plants themselves possess a mechanism to perceive signals, communicate, and respond to various abiotic stress factors, which are mediated by phytohormones ( Davies, 2010 ). A pleiotropic molecule, melatonin, has a significant role in mitigating the detrimental effects of abiotic stress, involving growth and development ( Liang et al., 2019 ), seed germination ( Castanares and Bouzo, 2019 ), root architecture ( Altaf et al., 2022 ), photosynthesis and antioxidant defense ( Anitha et al., 2023 ), stomatal regulation ( Jensen et al., 2023 ), and fruit yield and quality ( Dou et al., 2022 ). Several findings have investigated the effect of melatonin on physiological and biochemical mechanisms under individual drought or HT stresses ( Ibrahim et al., 2020 ; Jahan et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%